Current scenario of the wind energy in Pakistan challenges and future perspectives: A case study. (November 2016) - Baloch, Mazhar H.; Kaloi, Ghulam S.; Memon, Zubair A.
Abstract: Electricity plays an important role in the socioeconomic growth and social prosperity of any country. It is to be considered as the basic need for human development. Nowadays, low production of electricity is a serious problem in Pakistan, which directly restricts the development of the state. One-third of Pakistan's population does not have any electricity in the rural areas and about 10–12 hours load shedding in urban areas and is quite common. Although, the state of Pakistan always shows a deficit in the conventional resources, but no progress was also being made in the renewable resources such as the wind and solar energy. Therefore, it is better to utilize these natural assets in order to fulfill the electricity supply the country. In this manuscript, our main objective is to study and outlooks the country energy profile situation vis-à-vis wind energy potential characteristics of the most important wind corridor in the southern part of the country. Pakistan has around 1100 kilometers (km) coastal line for the wind energy potential, but in this manuscript, we have chosen one of the most suitable wind corridors of the southern part of the country. We also tried to prove theoretically that this wind zone is more favorable for country consumer demand. Moreover, future perspective and the major challenges during windmill implementation is also being discussed herein.